Pentingnya Memberikan Asi Ekslusif Untuk Kehidupan Bayi Dalam Perspektif Islam dan Kesehatan; Literatur Review - Dina Hasriyana; Endang Surani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Giving exclusive breast milk (ASI) to babies is an expression of God's love as well as an extraordinary gift for every baby born on earth and is the best way to create healthy and quality human resources. Currently, exclusive breastfeeding is not yet optimal and its coverage is still below the target set by the government and at present people pay less attention to the harmony between health and religious views. In the Qur'an Allah has confirmed the continuity of this breastfeeding for two whole years. This two-year period is a golden time span in terms of health and psychology for babies, which is found in the”Q.S. Al-Baqarah [2]: 233, Luqman [31]: 14, and Al-Ahqaf”[46]: 15. Breastfeeding plays a very important role in fulfilling infant nutrition so that it can increase the baby's immunity. Trace the international literature through electronic media with a keyword guide. 9 articles were selected, each representing the benefits of exclusive breastfeeding in the life of the baby from an Islamic and health perspective and providing various information. The results show that there are benefits of exclusive breastfeeding in the baby's life from an Islamic and health perspective. Conclusion Based on the analysis that has been done, there are benefits in giving exclusive breastfeeding to the baby's life both from an Islamic and health perspective.Keywords: Breastfeeding, exclusive breastfeeding, babies, benefits from an Islamic and health perspective AbstrakMemberikan Air Susu Ibu (ASI) Ekslusif pada bayi merupakan ungkapan kasih sayang Allah sekaligus anugerah yang luar biasa terhadap setiap bayi yang terlahir di muka bumi serta merupakan cara terbaik dalam menciptakan sumber daya manusia yang sehat dan berkualitas. Saat ini pemberian ASI Eksklusif belum optimal dan cakupannya masih di bawah target yang ditetapkan pemerintah dan pada masa kini manusia kurang memperhatikan keselarasan antara pandangan kesehatan dan agama. Dalam Al-Qur`an Allah telah menegaskan, kelangsungan penyusuan ini selama dua tahun penuh. Masa dua tahun ini merupakan rentang, waktu emas ditinjau dari segala sisi kesehatan dan kejiwaan bagi bayi”yakni terdapat dalam“Q.S. Al-Baqarah,”[2]: 233, Luqma,n [31]: 14, dan Al-Ahqaf”[46]: 15. Pemberian ASI sangat berperan dalam pemenuhan nutrisi bayi sehingga dapat meningkatkan kekebalan tubuh bayi. Lacak literatur internasional melalui media elektronik dengan panduan kata kunci 9 artikel dipilih, masing-masing mewakili manfaat memberikan ASI Ekslusif pada kehidupan bayi dalam perspektif Islam dan kesehatan dan berbagai memberikan informasi. Hasil yang menunjukkan adanya manfaat memberikan ASI Ekslusif pada kehidupan bayi dalam perspektif Islam dan kesehatan. Simpulan Berdasarkan analisa yang telah dilakukan terdapat manfaat dalam memberikan ASI Ekslusif pada kehidupan bayi baik dalam perspektif Islam dan kesehatan.Kata kunci: Menyusui, ASI Ekslusif, Bayi, Manfaat dalam Perspektif Islam dan Kesehatan.